Pre-treatment of textile wastewater in Van Phuc handicraft village by coagulation process - Vinh, Nguyen Dac; Noi, Nguyen Van; Boi, Lưu Van; Hanh, Nguyen Hong (VNU Journal of Science: Natural Sciences and Technology, 2006)
Abstract